Penerapan Media Smart Box sebagai Upaya Peningkatan Hasil Belajar Siswa Kelas V pada Materi IPAS Warisan Budaya SDN Sangen 02 Kabupaten Madiun - Kuni Kiromin Baroroh; Dwi Nila Andriani; Rahayu Diningsih (PT PUSTAKA CENDEKIA GROUP, 2025)
The low interest in learning for students is a challenge for a teacher. Starting from monotonous learning without learning media is one of the influences on student learning outcomes. To overcome this problem, researchers apply Smart Box media. The purpose of this study was to improve the learning outcomes of fifth grade students in the Cultural Heritage Science material at SDN Sangen 02 Madiun. The research method used was Classroom Action Research (CAR) as many as 2 cycles with 16 students. The data collection technique used was a test and the data analysis technique used was descriptive quantitative data analysis. The results of this study were that at the pre-cycle stage, the percentage results were 56.25%, the cycle I stage obtained a percentage result of 75%, while the cycle II stage obtained a percentage result of 90%. So it can be concluded that the application of Smart Box media can improve student learning outcomes.